Apresentação - De Santi, Valmir; Sales, Lúcia; Baía, Lorena; Saldanha, Márcia Regina Cardeal Gutierrez; Leite, Silvana; Machado, Silvio; Hiroshi, Wilson; Murakami, Israel; Bernardo, Noêmia Liege; Ferreira, Wesley Magno (Experiências Exitosas de Farmacêuticos no SUS, 2016)
Apresentação